The Role of Digital Transformation in Enhancing Institutional Commitment Among University Students: A Case Study of the Faculty of Economics and Political Science, Surman – Sabratha University (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the role of digital transformation in enhancing institutional commitment among university students, as it is a modern trend that can contribute to developing university administration and regulating the relationship between students and the educational institution. The study problem stems from the observation of an electronic system and digital services in the college, alongside the continued presence of some manifestations of weak student commitment to deadlines and procedures, attempts to circumvent some conditions, and the limited electronic implementation of some regulations, etc. The study adopted a descriptive-analytical approach and used a questionnaire consisting of two axes to measure digital transformation and institutional commitment. The questionnaire was distributed to a random sample of (200) individuals. The most important results showed that the level of digital transformation in the college was moderate, as was the level of institutional commitment among students. The study also demonstrated a statistically positive effect of digital transformation on institutional commitment and recommended linking electronic services to approved regulations so that conditions are applied uniformly and unjustified exceptions are minimized.
Keywords: Digital transformation, institutional commitment among university students.